Mexico's long crisis : toward new regimes of accumulation and domination. - McCAUGHAN, Edward J. (1993)
Focuses on the shift in capital accumulation strategy, imposed by the change in the accumulation process in advanced industrialized countries as well as by the exhaustion of Mexico's internal market, its inability to export competitively, and the inability of the political control mechanism crafted in the 1930s to control new social and political movements. Argues that there is need for a new strategy of political control involving the depoliticization of labour and peasant movements, and the reduction of corruption.